MothersProfilein Formula-FeedingTheir (LessThan Six Month) Infantsin Semarang - Yuliana Noor Setiawati Ulvie; Erna Kusumawati (Universitas Muhammadiyah Semarang, 2016)
Abstract.Babies given the infant formula in their first six monthswould likely encountered higher infant death risk thanthose who are given the exclusive breast milk. This lamely could happen since mothers were not well-informed about the advantages of breastfeeding, appropriate lactation technique, and sporadically rapid infant formula product marketing inthe society. This study aimed to identify mothers profiles in formula-feeding their (less than six months) infants inSemarang especially in PuskesmasBangetayu Kota Semarang. This study also employed explanatory observation retrospective design.The population of this study was 150 mothers of babies less than six months with formula feeding.From the population, there was 60 motherstaken as the sample of the study and the data was analyzed using Chi-Square test. Upon conducting the study, it could be known that there were 48 mothers (60%) who formula-feed their babies (less than six months) in PuskesmasBangetayuwere 21-35 years old, 27 mothers (45%) were only graduated from elementary school, 36 mothers (60%) were housewives, and 27 mothers (60%) were low-informed about the advantage of breast milk. It is suggested that mother should improve their knowledge and get enough information about breastfeeding since the regular antenatal care (ANC).